Activity Periods of Certain Fishes in Hirakud Reservoir - M.D., Varghese; A.A., Khan; V.C., George (Fishery Technology, 2025)
The activity of some common species of fish was studied on the basis of the number of fishes caught in gill nets between specific intervals. The results indicated that all the three species investigated, viz., Gudusia chapra, Osteobrama cotio cotio and Eutropiichthys vacha, were active during the first quarter of the day (00:00-06:00 h) and hence is the best period for harvesting these species by gill net.